2021
DOI: 10.20961/sepa.v17i2.38604
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Atribut Produk Kopi Bubuk Instan Indocafe Terhadap Kepuasan Dan Loyalitas Konsumen Di Kota Pontianak

Abstract: <div>This research aims to figure out the influence of the product attributes of</div><div>Indocafe and the effect on customer satisfaction and loyalty in Pontianak city. The</div><div>determination of the research location is determined intentionally (purposive method) in the city of Pontianak. The study used survey method with 150 respondents by using purposive sampling. Types of data used in this study are primary data and secondary data. Furthermore, the analysis is done by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
0
0
3
Order By: Relevance
“…It is concluded that the higher the customer satisfaction, the higher the customer loyalty, or vice versa, the lower the customer satisfaction, the lower the customer loyalty. This is in line with research conducted by [32], [33], [34], and [35]. If consumers are satisfied with the performance provided, it will make consumers loyal.…”
Section: Correlation Of Satisfaction and Consumer Loyaltysupporting
confidence: 90%
“…It is concluded that the higher the customer satisfaction, the higher the customer loyalty, or vice versa, the lower the customer satisfaction, the lower the customer loyalty. This is in line with research conducted by [32], [33], [34], and [35]. If consumers are satisfied with the performance provided, it will make consumers loyal.…”
Section: Correlation Of Satisfaction and Consumer Loyaltysupporting
confidence: 90%
“…Inovasi kemasan berpengaruh secara positif terhadap minat beli konsumen. Kemasan juga dapat memengaruhi loyalitas konsumen (Arista, Dolorosa, & Suharyani, 2021). Kemasan produk yang berbeda dari produk lainnya, dan memiliki informasi yang sesuai, akan mudah diingat serta dapat menarik minat konsumen untuk membeli.…”
Section: Kemasanunclassified
“…Menurut , menunjukkan bahwa product attribute mempengaruhi customer loyalty yang dapat diartikan harga dan kemasan sangat kuat dalam penentuan customer loyalty dan dapat disimpulkan adanya pengaruh yang signifikan antara product attribute dengan customer loyalty. Pada penelitian Arista et al, (2021) menjelaskan bahwa adanya pengaruh antara product attribute dengan customer loyalty serta menurut Astari et al, (2017) menunjukkan hasil yang sama yaitu product attribute berpengaruh terhadap customer loyalty.…”
Section: Hubungan Antara Product Attribute Dan Customer Loyaltyunclassified